Synthesis and Characterization of Silk Sericin / Acrylic Acid / Acrylamide Superabsorbent Polymer (Journal of Fiber Bioengineering and Informatics, 2018)
A composite superabsorbent material was synthesized based on silk sericin, acrylic acid and acrylamideby using N, N-methylenebisacrylamide (MBA) as the crosslinker and ammonium persulfate (APS) as theinitiator reagent. The water absorbency and water retaining properties of the composite under differentpreparation conditions were investigated. The absorbency of silk sericin / acrylic acid / acrylamide(SS/AA/AM) superabsorbent polymer polymer in deionized water, tap water and 0.9% NaCl solutionwere 285337 g/g, 191220 g/g, 3643g/g, respectively. SS/AA/AM material has excellent re-absorbentabilities and can be reused. The product showed different water absorbency in aqueous chloride saltsolutions with the order of Na^+ > Ca^{2+} > Mg^{2+} > Al^{3+}. FTIR spectra results indicated that silksericin was successfully grafted with acrylic acid and acrylamide molecules. The study on the absorbentmaterial based on sericin is useful for further research on biodegradable superabsorbent polymer.
Keywords: Absorbent Material; Silk Sericin ⁄ Acrylic Acid ⁄ Acrylamide; Water Absorbency; Water Retaining Capacity